Through the Looking Glass: A Scoping Review of Cinema and Video Therapy - Sacilotto, Elena; Salvato, Gerardo; Villa, Federica; Salvi, Fulvia; Bottini, Gabriella (Frontiers in Psychology, 2022)
Background: Cinematherapy and video treatments are artistic therapeutic techniques by which the individuals are exposed to their psycho-physical difficulties through the stories of the characters on the screen who are coping with the same issues that the patients are. Although these techniques are increasingly common within modern art therapies, there are neither comprehensive classifications of the different approaches nor agreement on their effectiveness. We performed a scoping review, describing different methodological approaches and outcome measures in cinematherapy and video treatments. Methodology: We searched articles in PubMed, PsycINFO and Google Scholar. We included: i) articles in which subjects were treated for their difficulties with videos or films, ii) articles written in English. Review articles and papers describing a research protocol without data collection were not included. Results: We analysed 38 studies. Thirty-six reported a positive effect of the treatment. Seven studies used classical cinematherapy, adopting a qualitative approach to measure the therapy outcome. Thirty-one studies used different video treatments, 8 of which were defined as randomised controlled trials with specific objective therapy outcomes. Studies were mainly focused on behavioural and psychological difficulties in Autism Spectrum Disorders and Schizophrenia. Conclusions: Studies using video treatments more often rely upon structured experimental designs; on the contrary, those who used classical cinematherapy produced descriptive results. A more standardised methodological approach in terms of experimental design, procedure, and objective outcome measure is needed to provide evidence on the effectiveness of these techniques, promoting its application in the clinical field.